Molecular mechanisms of peripheral nerve regeneration: emerging roles of microRNAs - Wu, Di; Murashov, Alexander K. (Frontiers in Physiology, 2013)
microRNAs are small non-coding RNAs that suppress gene expression through target mRNA degradation or translation repression. Recent studies suggest that miRNA plays an important role in multiple physiological and pathological processes in the nervous system. In this review article, we described what is currently known about the mechanisms in peripheral nerve regeneration on the cellular and molecular levels. Recently, changes in microRNA expression profiles have been detected in different injury models, and emerging evidence strongly indicates that these changes promote neurons to survive and shift their physiology from maintaining a structure and supporting synaptic transmission toward a regenerative phenotype. We reviewed the putative mechanisms involved in miRNA mediated post-transcriptional regulation and pointed out several areas where future research is necessary to advance our understanding of how targeting miRNA machinery can be used as a therapeutic approach for treating nerve injuries.